1989
DOI: 10.1200/jco.1989.7.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Similar efficacy of 6 and 18 months of therapy with four drugs (COMP) for localized non-Hodgkin's lymphoma of children: a report from the Childrens Cancer Study Group.

Abstract: Successful treatment of localized non-Hodgkin's lymphoma (NHL) in childhood with 18 months of cyclophosphamide, vincristine, methotrexate (MTX), and prednisone (COMP) prompted a randomized clinical trial to determine whether a 6-month course of the same therapy was as effective as an 18-month course when combined with local irradiation. Two successive Childrens Cancer Study Group (CCSG) protocols (CCG 551 and CCG 501) entered 232 eligible patients from October 1979 until April 1986. Initially, all children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…At the end of the 1970s, CNS-directed treatment was demonstrated to be unnecessary for localized stage abdominal tumors. [16][17][18] Our experience in …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the 1970s, CNS-directed treatment was demonstrated to be unnecessary for localized stage abdominal tumors. [16][17][18] Our experience in …”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of whether an additional course of HDMTX should be added to each COPAD course for resected Burkitt head and neck tumors, as is the case in other protocols that administer additional IT or an intermediate dose of MTX. 17,21,22 For patients with any stage I and II lymphoma, except for the lymphoblastic type, the Pediatric Oncology Group (POG) recently confirmed that 3 courses of CHOP was as efficient as the same treatment with local radiotherapy or maintenance therapy, yielding an EFS of 89% Ïź 8%. 21,23 In LMB89, the EFS rate for such stages is 97% (95% CI, 92%-99%).…”
mentioning
confidence: 99%
“…[7][8][9][10][11] The distribution of the pathologic subtypes of lymphoma among children is remarkably different from that in adults. [12][13][14] In children, the most common subtypes are aggressive lymphomas such as lymphoblastic lymphoma, diffuse large B-cell lymphoma, Burkitt lymphoma, anaplastic large-cell lymphoma, and peripheral T-cell lymphoma. [12][13][14] However, extranodal nasal-type NK/T-cell lymphoma is extremely rare among children, although this condition is frequently diagnosed in male adults with the median age of approximately 45 years.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] In children, the most common subtypes are aggressive lymphomas such as lymphoblastic lymphoma, diffuse large B-cell lymphoma, Burkitt lymphoma, anaplastic large-cell lymphoma, and peripheral T-cell lymphoma. [12][13][14] However, extranodal nasal-type NK/T-cell lymphoma is extremely rare among children, although this condition is frequently diagnosed in male adults with the median age of approximately 45 years. [7][8][9][10][11] Extranodal nasal-type NK/T-cell lymphoma shows an aggressive clinical course with distinct clinicopathologic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Children with limited stage NHL have an excellent prognosis with an estimated 5-year event-free survival (EFS) of 90-95%. [10][11][12][13] The prognosis for advanced stage disease has also improved and varies based on subtype (60-90% 5-year EFS). 11,[13][14][15][16][17][18][19][20][21][22] HD Patients with HD commonly present with cervical or supraclavicular lymphadenopathy and most will present with some degree of mediastinal involvement.…”
Section: Nhlmentioning
confidence: 99%